1992
DOI: 10.3109/01485019208987721
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surgical Repair of Experimental Left Varicocele on Testicular Temperature, Spermatogenesis, Sperm Maturation, Endocrine Function, and Fertility in Rabbits

Abstract: To evaluate the effectiveness of surgical correction of varicocele in restoring the function of the varicocelized testicle, experimental varicoceles were created in 16 male rabbits by partly ligating the left lumbotesticular trunk. Five control rabbits received a sham operation (group A). Two months later, eight of the varicocelized rabbits underwent surgical repair by ligation and cutting of the dilated left testicular vein (group B). The remaining eight varicocelized animals did not receive any additional tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
8

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 28 publications
2
23
0
8
Order By: Relevance
“…Sofikitis and Miyagawa observed that the surgical repair of an experimental varicocele in the rabbit can significantly improve the parameters indicating the harmful effects of the varicocele on the testicles (22). In addition, while studying animal models researchers had observed that the surgical repair of the secondary right varicocele improved all semen parameters indicating the harmful consequences of the primary induced left varicocele on the right testis (23).…”
Section: Discussionmentioning
confidence: 99%
“…Sofikitis and Miyagawa observed that the surgical repair of an experimental varicocele in the rabbit can significantly improve the parameters indicating the harmful effects of the varicocele on the testicles (22). In addition, while studying animal models researchers had observed that the surgical repair of the secondary right varicocele improved all semen parameters indicating the harmful consequences of the primary induced left varicocele on the right testis (23).…”
Section: Discussionmentioning
confidence: 99%
“…Les temp6ratures testiculaires moyennes droite et gauche sont significativement augment6es dans la population d'animaux apr~s cr6ation d'une VGE, par rapport aux animaux t6moins, que ce soit chez le rat [32,9,10,18,19,34,43,44,16,17], le singe [21,13,14], le chien [32] ou le lapin [35,36]. Cette augmentation de la temp6rature testiculaire moyenne n'est pas un ph6nom~ne transitoire puisqu'elle est toujours pr6sente 3 ou 6 mois aprbs la cr6ation d'une VGE chez le rat [18,17], le chien [32] ou le lapin [35], voire 3 ans chez le singe [13,14].…”
Section: D O N N E E S a N I M A L E Sunclassified
“…Cette augmentation de la temp6rature testiculaire moyenne n'est pas un ph6nom~ne transitoire puisqu'elle est toujours pr6sente 3 ou 6 mois aprbs la cr6ation d'une VGE chez le rat [18,17], le chien [32] ou le lapin [35], voire 3 ans chez le singe [13,14]. Deux arguments font que cette augmentation des temp6ratures moyennes testiculaires est bien une cons6quence de la cr6ation d'une VGE : a) les populations d'animaux sham-op6r6s (i.e.…”
Section: D O N N E E S a N I M A L E Sunclassified
“…It is found in about 15% of the general population, in 35% of men with primary infertility and in 70-80% of men with secondary infertility. A significant improvement in the parameters indicating harmful effects of the varicocele on the testicles is shown after surgical repair of experimental varicoceles in rabbits [1] . There are experimental studies focusing on the effects of unilateral varicocele with bilateral physiologic and histologic changes in both testicles as well as others aiming to analyze the effects of retrograde adrenal metabolites flow on testicular damage [2,3] .…”
Section: Introductionmentioning
confidence: 99%